(3UMjM eSdes - (3GdbTjQj GdfjSGHhQqi, CHh GdMSjf, eSde Hf GdMLGL Hf eSde, J (B261 (3g`s ((3Ydj GdhUjaj Hf eMeO GdHQhShjs)
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH GdHjhY HGH EHWGd HjY GdedGeSI hGdefGHPI MOKfG jMji Hf jMji GdJejej bGd bQCJ Ydi eGdc Yf eMeO Hf jMji Hf MHGfs
(3BNQgG (B:s
(3MOKfG YHO GdQMefejYG Yf SajGf Yf CHj gGTe Yf CHj eLdR Yf bjS Hf YHGO bGd SeYJ CHG PcQ QVj Gddg Yfg jbSe dfRdJ gPG NUeGf HeKd MOjK gTGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 221s
(3eYLe GdeDdajf (B3 / 851s
(3cTa GdXfhf (B1 / 555s
(3TPQGJ GdPgH (B2 / 144s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs